The Effect of Small Business Innovation and the Role of Government on the Environment: Evidence from Indonesia - Chaniago, Harmon (International Journal of Energy Economics and Policy, 2021)
This study aims to analyze individual and organizational innovation in small businesses and their impact on the environment. The focus of the analysis is also expanded on how to engineer the innovations that exist in small businesses through consumer behavior so that the engineering carried out is effective in protecting the environment. The role of the government is used as a regulator in a country. The research was conducted using a quantitative descriptive method, then continued with a document study on the Indonesian government's environmental regulations. The research was carried out during the Covid-19 pandemic in a sizeable Indonesian city, namely Bandung City. The study results show that small businesses' individual and organizational innovation play a role in determining environmental conditions. Government engineering to change consumer behavior and consumer needs is very effective in changing the behavior of entrepreneurs to go green and green business. Keywords: Individual innovation, organizational innovation, environment, small business, government engineering JEL Classifications: O36, F18, Q58 DOI: https://doi.org/10.32479/ijeep.11808